2004
DOI: 10.1002/jsfa.1891
|View full text |Cite
|
Sign up to set email alerts
|

Storage and ultraviolet‐induced tissue stress effects on fresh‐cut pineapple

Abstract: The effect of UV-induced stress on the volatile aroma compounds in cut pineapple was compared with that of storage at 4 • C for 24 h. Eighteen volatile compounds were identified by solidphase microextraction (SPME) in fresh-cut pineapple. Methyl-2-methylbutanoate, methyl hexanoate, methyl 5-hexenoate, ethyl hexanoate and ethyl 5-hexenoate were the major aroma compounds. Storage at 4 • C for 24 h, and exposure of cut fruit to UV radiation for 15 min caused a considerable decrease in the concentration of esters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Furthermore, Lamikanra and Richard (2004) reported that the UV treatment of fresh cut pineapple caused a considerable decrease in the concentration of esters and an increase in the relative amount of copaene (sesquiterpene). Moreover, the stimulation of terpene biosynthesis by stress e.g.…”
Section: Terpenes and Ketonesmentioning
confidence: 98%
“…Furthermore, Lamikanra and Richard (2004) reported that the UV treatment of fresh cut pineapple caused a considerable decrease in the concentration of esters and an increase in the relative amount of copaene (sesquiterpene). Moreover, the stimulation of terpene biosynthesis by stress e.g.…”
Section: Terpenes and Ketonesmentioning
confidence: 98%
“…Moreover, such technology has been reported to inactivate oxidative and pectolytic enzymes in fresh-cut apple derivatives . UV-C radiation was also shown to modify the flavour pattern of tropical fruits (Beulieu, 2007;Lamikanra & Richard, 2004) as well as to catalyze the oxidative damage of flavour and pigments (Hashizume, Gordon, & Mottram, 2007;Manzocco, Kravina, Calligaris, & Nicoli, 2008). Thus UV-C treatment potential for commercial use would depend on its ability to sanitize and retard microbial growth without causing undesirable quality changes in the final product (Fonseca & Rushing, 2006).…”
Section: Introductionmentioning
confidence: 96%
“…h) Coinjection of compounds tested in f and g. i) Synthetic methyl (2R,6R)-2,6,10-trimethylundec-9-enoate (51). j) Coinjection of compounds tested in g and i. methyl esters of A and B occur in pineapple [39]. The norterpenoid E has been found in peppermint oil [40], while its unsaturated analog F (with unknown configuration) was found in the skin extracts of the opisthobranch mollusc, Melibe leonina [41], and in the sex-attracting secretion of the dung beetle, Kheper lamarcki [42].…”
Section: Methyl Ester Of J (Methyl-j) the Synthesis Of (S)-48-dimetmentioning
confidence: 98%